The Influence of Service Quality and Perceived Value on Customer Loyalty - Elizabeth, Elizabeth; Santoso, Wawa (Journal La Sociale, 2026)
This study aims to examine the influence of service quality and perceived value on customer loyalty to Uniqlo products in TikTok stores. The research method used was a quantitative approach with a survey technique. Data were collected by distributing questionnaires to 210 TikTok users in Indonesia via Google Form. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results show that service quality and perceived value have a positive and significant effect on customer loyalty. The implications of this study emphasize that companies must emphasize consistent service quality and create perceived value that is relevant to customer needs. This will strengthen customer loyalty.